Correlates of Social Isolation Among Community-Dwelling Older Adults During the COVID-19 Pandemic - Adepoju, Omolola E.; Chae, Minji; Woodard, LeChauncy; Smith, Kendra L.; Herrera, Luz; Han, Daikwon; Howard, Daniel L.; Dobbins, Jessica; Ory, Marcia (Frontiers in Public Health, 2021)
Background: The past year has severely curtailed social interactions among older adults given their high rates of COVID-19 morbidity and mortality. This study examined social, behavioral, and medical correlates of social isolation among community-dwelling older adults during the COVID-19 pandemic and stratified findings to explore unique differences in two typically neglected populations, African American and Hispanic older adults. Methods: Working with community-based organizations and senior living centers, the research team administered a survey to older adults 55 years of age and older (n=575). The survey assessed COVID-19 prevention behaviors, medical conditions, and lived experiences, including feelings of social isolation, in the target population. Responses to a previously validated social isolation question informed a dichotomous social isolation dependent variable. Multivariable logistic regression was used to adjust for sociodemographic characteristics, medical conditions, unmet caregiving needs, and COVID-19 prevention behaviors. Results from the regression model were stratified by race/ethnicity to examine correlates of social isolation in African American and Hispanic older adults, separately. Results: Overall, female sex and a higher level of education were also positively associated with social isolation (OR=2.46, p=0.04; OR=5.49, p=0.02) while having insurance exhibited an inverse relationship (OR=0.25, p=0.03). Unmet caregiving needs were strongly associated with social isolation (OR=6.41, p<0.001) as was having any chronic conditions (OR=2.99, p=0.02). Diabetes was the single strongest chronic condition predictor of social isolation. Among minority older adults, a different pattern emerged. For Hispanic older adults, language, unmet caregiving needs, and social distancing were strongly associated with social isolation; while unmet caregiving needs, having 1+ chronic conditions and adhering to social distancing guidelines were significant predictors in African American older adults. Conclusion: These findings suggest that social isolation affects older adults in a myriad of ways and support the need for culturally sensitive initiatives to mitigate the effect of social isolation in these vulnerable populations.